Strategi Pengelolaan Pegunungan Jawa: Studi Kasus Pegunungan Dieng Jawa Tengah, Indonesia - Nur Sumedi; Hasanu Simon; Djuwantoko (Foresty Faculty of Hasanuddin University, 2012)
This research was conducted in Dieng Mountains region of Central Java Province, from August 2007 to December 2008. The purpose of this research was to find the optimal management strategy. Strategy Analysis using the SWOT technique. The results showed that the management of the Dieng Mountains region should consider the priorities and strategies that were urgently needed to improve effective communication among stakeholders. While for the other six strategic priorities were: (1) Finding and applying the optimal model of land use (economic, social, ecological), (2) Eliminate sectoral barriers to jointly harness the potential from outside the area, (3) Enhance the institutional competence to exciting role of institutions of all levels, (4) Improving the quality and quantity of human resources management of mountain areas; (5) Increasing the role of a forum for dialogue by taking the experience of history; (6) Increase the environmental awareness program with a realistic field implementation.